Predator preferences: a key to effective biological control design - Steven, Winnie; Ombeni, Kishimbo; Kweka, Eliningaya J.; Kimirei, Merikinoi; Cleopa,, Cecilia (Journal of Health & Biological Sciences, 2021)
Objetctive: This experimental study aimed to assess the preference of Gambusia affinis to mosquito larvae of An.gambiae s.s., Cx. quinquefasciatus and Aedes aegypti. Method: Three Gambusia affinis were introduced in a glass container with a dimension of 45cm x 25cmx 25cm. Three larvae densities were used, 90 (30 larvae per species), 120 (40 larvae per species), and 180 (60 larvae per species). Each density experiment was set in triplicate and monitored after 1, 2, 3, and 24 hours. No fish food was added to the container for larvae. Results: Results have shown that in all times A. aegypti has been the most preferred species by Gambusia affinis. Among the tested species, A. aegypti was most prayed with time and in different densities. In mixed models including density, species, and time there was no significant difference among the species predation. Conclusion: Preliminary results have shown that the appropriate choice of predators for each mosquito species can have a great impact on bio-control to substantially complement existing tools.